Quality of life of patients undergoing hemodialysis - Garofyllou, Georgia; Kelesi, Martha; Gerogianni, Georgia; Tsaras, Konstantinos; Fasoi, Georgia; Kaba, Evridiki; Stavropoulou, Areti (Health & Research Journal, 2017)
Introduction: Chronic Renal Failure (CRF) is a chronic disease, which has a negative impact on the quality of patients’ life. The study of factors affecting the quality of life of these patients is necessary to investigate the impact of the disease in a biological, psychological and social level. Aim: The purpose of this research study was to investigate the satisfaction of patients undergoing chronic hemodialysis and their perceptions of their quality of life. Material and Method: The study sample consisted of patients undergoing chronic hemodialysis at a Dialysis Unit in Athens. The study lasted from January 2016 to March 2016. To measure the health related quality of patients’ life, the Greek version of the questionnaire WHOQOL-BREF of the World Health Organization was used. The completion of the questionnaires was made by the method of the structured interview. A total of 70 questionnaires were completed. Results: According to the study results, most of the patients considered the quality of their life as good (48.6%), while the 8.5% described it as bad or very bad. The lowest satisfaction rates associated with issues of physical health and independence with mean (12.89 ± 2.23) and the highest with social relations (14.68 ± 1.50). Conclusion: The effect of Chronic Renal Failure on the physical, psychological and social background of patients on dialysis is an essential factor in creating a tailor-made holistic treatment program, adjusted to the specific needs of each patient.